Promoting the importance of aquatic foods on human nutrition and public health under APART in Assam - Ratha, Baishnaba; Sonowal, Nabamika; Beypi, Neeta; Sarma, Sanjay; Rajendran, Suresh; Chadag, Vishnumurthy Mohan; Shenoy, Neetha; Dubey, Sourabh; Panemangalore, Arun (WorldFish, 2023)
One of the key activities (Deliverable 7) under the APART project is “Improving impact of aquaculture and beel fisheries on human Nutrition”. WorldFish with partners is supporting the implementation of this activity. This consolidated report summarizes all the work done by WorldFish and partners as part of deliverable 7. The project has developed and tested several Social Behavioural Change Communication (SBCC) resources (e.g. banners, leaflets, brochures, calendars, TV spots, and videos) to promote the consumption of aquatic foods by vulnerable communities, PLM, adolescent girls, and children by targeting relevant stakeholders (e.g. Integrated Child Development Services programs, District Social Welfare (DSW) field functionaries, Anganwadi workers, Village communities, primary health centres, and the general public). We have trained 597 trainers to spread the message on the role of aquatic foods. We conducted 36 cluster-level awareness programs where 1994 numbers of women, adolescent girls and community people were given information on the benefits of fish consumption. We also organised 2 zonal workshops and 1 statelevel workshop for different stakeholders to build awareness of the importance of aquatic foods. Based on the demonstrations at the community level, the project documented all the small fish-based recipes cooked locally at the community level and produced a Small Fish Recipes book.